Acute coronary syndromes in patients with active hematologic malignancies – Incidence, management, and outcomes. (15th January 2019) - Park, Jae Yoon; Guo, Wei; Al-Hijji, Mohammed; El Sabbagh, Abdallah; Begna, Kebede H.; Habermann, Thomas M.; Witzig, Thomas E.; Lewis, Bradley R.; Lerman, Amir; Herrmann, Joerg
Abstract: Background: Cancer and cardiovascular diseases are the two leading causes of death in industrialized countries. Optimal management of life-threatening presentations of both of their diseases can pose significant challenges. The current study aimed to address the incidence, management, and outcome of acute coronary syndromes (ACS) in patients with active hematological malignancies. Methods: This retrospective registry-based cohort study included adults with active leukemia or lymphoma who were hospitalized at Mayo Clinic Rochester from 01/01/2004 to 12/31/2014. The diagnosis of ST-segment elevation MI (STEMI) or non-ST-segment elevation MI (NSTEMI) was made based on the 3rd Universal Definition for MI, or of unstable angina (UA) in the absence of cardiac troponin elevation. Main outcome measures included all-cause, cardiac, and non-cardiac death in-hospital and at one year. Results: Of 5300 adult patients with active hematological malignancies, 73 (1.4%) were diagnosed with an ACS (78.1% NSTEMI and 13.7% STEMI). 17.5% and 40% of NSTEMI and STEMI patients underwent coronary angiography, with percutaneous coronary intervention in 5.3% and 30%, respectively. While >80% of patients received β-blocker therapy, only half of all and <50% of patients managed "medically" received antiplatelet, anticoagulant, and/or statin therapy. The in-hospital and 1-year mortality was 21.9% and 58.9%, respectively, of which 25% and 15% were cardiac in etiology. Aspirin, beta-blocker, statins, and angiotensin-converting enzyme inhibitor/angiotensin-II receptor blocker were associated with better mortality outcomes. Conclusions: In a large, contemporary study of adults with active hematologic malignancies, ACS was uncommon, but commonly managed not in keeping with societal guideline recommendations. Highlights: ACS in patients with hematologic malignancies is not common but commonly managed not in keeping with practice guidelines Aspirin, beta-blocker, statin, ACE inhibitor/ARB blocker use is associated with better mortality in this patient population Predominant cause of death is non-cardiac, but 25% of all in-hospital and 15% of all 1-year deaths are cardiac in nature